Knowledge Transfer and Innovation in the Batik Industry - Dwimahendrawan, Andrias; Sampir Andrean Sukoco; Ali Wafa (ITB AAS Indonesia Surakarta, 2025)
This study is an in-depth study of the previous year's research which aims to explain in detail about: (i) The process of knowledge creation in the typical batik business in East Java, namely in Jember Regency; (ii) The relationship between knowledge creation and innovation in the typical batik business of East Java, in Jember Regency, which is unique compared to other regions; (iii) Formulating a strategic architecture for the creation of knowledge and company innovation that occurs in the typical batik business of Jember, East Java, Jember from the perspective of knowledge management theory. Data were obtained using observation and in-depth interviews, then analyzed using a descriptive analytical approach. The results of the study found. The process of making batik is generally not carried out in one business unit, but almost every process is separate from one another. The source of innovation comes more from outside because the knowledge creation process in the organization is less than optimal. The knowledge creation that takes place in the Jember batik business is therefore more driven by external factors